The Role of Teamwork in Achieving Organizational Goals: Lessons from the Ramayan (ART ORBIT, 2025)
This study examines the enduring epic, the Ramayan, as a strategic and philosophical framework for enhancing the understanding and application of cooperation in contemporary businesses. The study examines how the collaborative endeavors in the Ramayan specifically the coordination among Lord Ram, Lakshman, Hanuman, Sugreev, and the Vanar Sena-reflect effective teamwork concepts observed in contemporary organizational contexts. This research investigates the impact of loyalty, communication, leadership, shared vision, and role clarity on organizational success through a survey of professionals, educators, and students in Ajmer and Beawar. A mixed-method approach was employed, utilizing both quantitative and qualitative instruments. Data from 250 respondents were subjected to analysis by descriptive statistics and correlation testing. Research demonstrates that firms adopting principles consistent with those in the Ramayan-such as goal alignment, servant leadership, and mission-driven collaboration-experience enhanced team happiness and productivity. This study promotes the integration of cultural narratives into leadership development and teamwork training, enhancing the comprehension of Indian Knowledge Systems (IKS) within modern corporate practices